Comparison between the human reactions in a simulacrum and in a real fire situation - Cordeiro, Elisabete da Cunha (2018)
Human reaction to a fire situation in buildings depends on the characteristics of each individual, of the building and the actual emergency situation. To minimize the consequences of an emergency fire situation in a building, it is important to have a safe, orderly and rapid evacuation. For this purpose the occupants should be trained to respond in an appropriate way. Therefore, it is necessary to assess whether simulacrums or fire drills are effective or not. In recent years, in Portugal, the number of fire simulacrums in office buildings, schools and hotels, among others, have increased. Taking as reference the Portuguese population, this article presents the results of an ongoing research project that compares the human behavior in a real fire situation with that observed in a fire simulacrum. The study was supported by a significant number of surveys conducted to the occupants who were involved in one of the two previous mentioned situations. The comparison between the actions undertaken by the occupants in both situations allows understanding if human behavior in a simulacrum reflects human behavior in a real fire situation.